Psychoactive drug advertising: a comparison of technical information from three countries: Brazil, United States and United Kingdom - Mastroianni, Patricia de Carvalho; Galduróz, José Carlos Fernandes; Carlini, Elisaldo Araujo (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Studies carried out in the 1970s and 1980s showed that there were country-dependent disparities in the information given for the same drug in medical advertise- ments. National and international regulations have been published to do away with such dis- parities and to foster the rational use of drugs. The purpose of this study was to compare the informa- tion contained in psychoactive drug advertise- ments published in psychiatric journals in Brazil, the United States and the United Kingdom, before and subsequent to the publication of the United States Export Act, in 1986, the WHO criteria, in 1988, and the Brazilian Sanitary Surveillance Agency Resolution no. 102, in 2000. TYPE OF STUDY AND SETTING: Content analysis, at Centro Brasileiro de Informações sobre Drogas Psicotrópicas (Cebrid). METHODS: We gathered advertisements from Brazilian, American and British psychiatry periodi- cals published before and after each ruling. We analyzed a total of twenty-four Brazilian advertise- ments that were for the same psychoactive drugs as advertised in American and/or British publications from the same period. RESULTS: We observed that Brazilian advertise- ments omitted information on usage restrictions, such as contraindications, adverse reactions, interactions, warnings and precautions, and that such information was present in American and British advertisements. CONCLUSIONS: The data suggest that disparities in the information given for the same drug still persist. The information depends on the country in which each drug is marketed. The legislation is insufficient for eradicating such disparities.